Incesto y reversión colonial en Mapocho de Nona Fernández. - GARCÍA MENDOZA, FRANCISCO (Nomadías)
This essay shows that the incestuous approaches of the brothers in Mapocho (2002) by Nona Fernández is an act of insubordination against the established orders and norms. Thus, the incestuous act of the protagonists not only threatens to crack the foundations of any possible place of family institutionality but is also articulated as an act that tries to reverse the colonial matrix that sustains the nation they inhabit. Tho show this, an analysis of the relationship between the siblings and the mother is proposed, crossed with some approaches by Sonia Montecino and Michel Foucault.